(untitled) (Jurnal Agroekoteknologi dan Agribisnis, 2022)
Regarding of Statistic Pekanbaru in 2019, the goat population in Payung Sekaki Subdistrict are 329 heads. The goat population can be improved by feed manipulation technique to increase goat productivity. One of feed manipulation technique is probiotic supplementation. The study aims to analyze body weight gain and feasibility of goat fattening analysis supplemented Bioplus probiotic. The study was designed in Randomized Block Design with 3 treatments and 4 replications. The treatments such us P0 = control (field grass), P1 = control + Bioplus 100 g, P2 = control + Bioplus 150 g. The variables measured was average daily gain (ADG) and business analysis such us income, Break Even Point (BEP) production, BEP price, Revenue Cost Ratio (R/C ratio) and Benefit Cost Ratio (B/C ratio). ADG data was analysis by Anova and Least Significant Difference. The result showed that the supplementation Bioplus probiotics increase daily gain of goat with the average of daily gain respectively P0 53,13 g/head/day, P1 95,63 g/head/day dan P2 127,50 g/head/day. The result of feasibility analysis showed that P2 has the highest income Rp840.800,- R/C ratio 1.140 (>1) and P0 with income Rp15.000,- with R/C ratio . Supplementation of Bioplus probiotic with dose 150 g/head/day increased average daily gain and increased income to provide better business feasibility of fattening goat.